Recent advances in the management of pulmonary sarcomatoid carcinoma. (2nd April 2016) - Shum, Elaine; Stuart, Matthew; Borczuk, Alain; Wang, Feng; Cheng, Haiying; Halmos, Balazs
ABSTRACT: Pulmonary sarcomatoid carcinoma (PSC) is a unique and biologically fascinating group of poorly differentiated non-small cell lung cancer (NSCLC), however it is highly aggressive with poor overall survival compared to other types of NSCLC. Radical surgery remains the standard of care for early localized disease but this has shown to result in high recurrence rates. Traditional palliative chemotherapy is associated with poor response in advanced/metastatic PSC. Recent comprehensive genetic studies and clinical observations are starting to elucidate the key oncogenic underpinnings of PSC. In particular, the recent identification of frequent genetic alterations of the MET gene leading to exon 14 skipping have yielded actionable targets for intervention with available MET inhibitors for a subset of PSC patients. Immunotherapy against immune checkpoints, such as anti-PD1/PD-L1 agents, have also raised great interest for the management of PSC. A growing understanding of the molecular pathogenesis of PSC is rapidly yielding novel approaches for the treatment of this deadly malignancy.